Suriname : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper for Suriname describes the structure of the financial system, and provides a preliminary assessment of the conditions of the banking system. It highlights the need for a comprehensive public sector reform, targeting both the civil service and the public enterprises, and reviews the recent policy developments and financial sector reforms. It also provides the IMF's projections and estimates for Suriname on central government operations in percent of GDP; central government revenues, grants, and expenditure in billions of guilders and in percent of GDP; summary accounts of the banking system, and so on.